INSTRUCTORS Raffi Hovasapian John Zhu

Enter your Sign on user name and password.

• Follow us on:
Start learning today, and be successful in your academic & professional career. Start Today!
This is a quick preview of the lesson. For full access, please Log In or Sign up.
For more information, please see full course syllabus of Calculus AB

• ## Related Books

 2 answersLast reply by: Yong Su AnTue Feb 24, 2015 2:03 PMPost by Orsolya KrispÃ¡n on April 10, 2013you turned the negative sign into a positive one. in example 5.

### Integrals Basic Rules of Integration

• Constant rule:
• Constant multiple rule:
• Addition and difference rule:
• Exact same rules as derivatives!

### Integrals Basic Rules of Integration

∫7  dx
• ∫7  dx = 7 ∫dx
• ∫7  dx = 7(x + C)
∫7  dx = 7x + c
∫9x  dx
• ∫9x  dx = 9 ∫x  dx
• ∫9x  dx = 9([(x2)/2] + C)
∫9x  dx = [9/2] x2 + c
∫(9x + 7) dx
• ∫(9x + 7) dx = ∫9x  dx + ∫7  dx
• ∫(9x + 7) dx = 9 ∫x  dx + ∫7  dx
• ∫(9x + 7) dx = 9 ([(x2)/2] + c1) + 7x + c2
• ∫(9x + 7) dx = [9/2] x2 + 7x + c3 + c2
• We can combine the two constants into a new constant
∫(9x + 7) dx = [9/2]x2 + 7x + c
∫(9x − 7) dx
• ∫9x − 7 dx = ∫9x  dx − ∫7  dx
• ∫9x − 7 dx = 9 ∫x  dx − ∫7  dx
• ∫9x − 7 dx = 9 ([(x2)/2] + c1) − 7x − c2
∫9x − 7 dx = [9/2]x2 − 7x + c
∫2 x3 dx + 2 ∫x3 dx
• ∫2 x3 dx + 2 ∫x3 dx = 2 ∫x3 dx + 2 ∫x3 dx
• ∫2 x3 dx + 2 ∫x3 dx = 4 ∫x3 dx
• ∫2 x3 dx + 2 ∫x3 dx = 4 ([(x4)/4] + C)
∫2 x3 dx + 2 ∫x3 dx = x4 + c
∫x5 − x7 dx
• ∫x5 − x7 dx = ∫x5 dx − ∫x7 dx
• ∫x5 − x7 dx = [(x6)/6] + c1 − ([(x7)/7] + c2)
∫x5 − x7 dx = [(x6)/6] − [(x7)/7] + c
∫3 x2 − 2x + 5 dx
• ∫3 x2 − 2x + 5 dx = 3 ∫x2 dx − 2 ∫x  dx + 5 ∫ dx
• We can skip a couple of steps by combining the constants ahead of time.
• ∫3 x2 − 2x + 5 dx = 3 [(x3)/3] − 2 [(x2)/2] + 5x + c
∫3 x2 − 2x + 5 dx = x3 − x2 + 5x + c
∫√{4x} dx
• ∫√{4x} dx = ∫√4 √x dx
• ∫√{4x} dx = ∫2 √x dx
• ∫√{4x} dx = 2 ∫x[1/2] dx
• ∫√{4x} dx = 2 ([(x[1/2] + 1)/([1/2] + 1)]) + c
• ∫√{4x} dx = 2 ([(x[3/2])/([3/2])]) + c
∫√{4x} dx = [4/3] x[3/2] + c
∫1 − [(x2)/2] + [(x4)/24] dx
• ∫1 − [(x2)/2] + [(x4)/24] dx = ∫dx − [1/2] ∫x2 dx + [1/24] ∫x4 dx
• ∫1 − [(x2)/2] + [(x4)/24] dx = x − [1/2] [(x3)/3] + [1/24] [(x5)/5] + c
∫1 − [(x2)/2] + [(x4)/24] dx = x − [(x3)/6] + [(x5)/120] + c
Find [d/dx] (x − [(x3)/6] + [(x5)/120])
• [d/dx] (x − [(x3)/6] + [(x5)/120]) = 1 − [(3x2)/6] + [(5x4)/120]
[d/dx] (x − [(x3)/6] + [(x5)/120]) = 1 − [(x2)/2] + [(x4)/24]

*These practice questions are only helpful when you work on them offline on a piece of paper and then use the solution steps function to check your answer.

### Integrals Basic Rules of Integration

Lecture Slides are screen-captured images of important points in the lecture. Students can download and print out these lecture slide images to do practice problems as well as take notes while watching the lecture.

• Intro 0:00
• Basic Rules of Integration 0:09
• Constant Rule
• Example 1
• Addition and Difference Rule 1:40
• Example 2
• Example 3: Subtraction/ Difference Rule 2:47
• Example 4 3:55
• Example 5 5:19
• Example 6 7:37